Individualism-Collectivism (IC) as an Individual Difference Predictor of Organizational Citizenship Behavior (OCB) in an Accounting Environtment Setting - Susanti R. Saragih; Joni . (Jurnal Manajemen Maranatha, 2007)
The purpose of this research is to examine whether individualism-collectivism dimension (beliefs, values and norms) positively related with organizational citizenship behavior dimension (interpersonal helping, individual initiative and loyal boosterism) in an accounting environment setting. Structural Equation Model (SEM) are used to analyze data. The sample consists of 365 accounting college students. The results showed that individualism-collectivism‟s dimension positively related with organizational citizenship behavior dimension. This result supported the previous research conducted by Moorman and Blakely (1995).